Partisipasi Mahasiswa Kuliah Kerja Nyata Dalam Menyuarakan Gerakan Anti Bullying Pada Anak-Anak di Sekitar Wilayah Alun-Alun Sidoarjo dan Taman Bungkul Surabaya - Nadia Faizah Putri Devina; Mira Diva Prasyanti; Miskha Ainun Nisa; Edghar Abdullah Albab; Adhitya Widya Kartika (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Kuliah Kerja Nyata (KKN) is a form of student activity in higher education, which is also part of education and has the aim of doing community service. Community service in this paper refers to the activities of the author's group, which conducts empirical study practices, by directly carrying out socialization activities to the community related to the dangers of bullying for children. This activity is deemed necessary to overcome the phenomenon of moral degradation that occurs in children. Through this activity, the authors try to campaign to children, teenagers, and parents around Sidoarjo Square and Surabaya Bungkul Park, to break the chain of bullying in the scope of children's friendship, because moral degradation itself is a trigger for bullying or discrimination against someone, in this case children in the scope of their friendship. This activity is carried out solely for education and community service, as well as an effort to foster the moral quality of the nation's young generation. From this activity, the author can say that socialization is the right method to do in shaping children's morals through the delivery of informative and interesting material.